Levelling up: towards decolonising apprenticeship learning. (15th March 2023) - Beaudry, Jean-Luc; Perry, J. Adam
ABSTRACT: With a focus on the Western-Canadian province of Manitoba, this article aims to develop a conceptual and empirical exploration of how apprenticeship learning can be transformed to meet the needs of Indigenous apprentices. Conceptually, the article layers an articulation of decolonising education onto apprenticeship learning in such a way as to explicitly support apprentices' prior knowledge and recognise the socio-political context within which apprenticeship learning occurs. Empirically, the article draws on qualitative in-depth interviews with Indigenous carpentry apprentices about their experiences with on-the-job training in order to better understand how Indigenous adult learners negotiate well-documented systemic barriers to education and employment. By contrasting participants' experiences in industry worksites to their experiences with Indigenous-centric curriculum offered by the Manitoba-based social enterprise BUILD, the article develops a discussion of how market-driven apprenticeship programmes limit the potential achievements of Indigenous learners and how a decolonising approach to apprenticeship learning that prioritises Indigenous epistemologies may result in higher levels of learner success.